Pengaruh Rebusan Daun Sirsak Terhadap Tekanan Darah Pada Wanita Usia Subur Penderita Hipertensi Di Wilayah Kerja Puskesmas Martapura 1 - Nugraha, Fir'ad Setya; Sukmawaty, Martini Nur; Pusparina, Iis; Raziansyah, Raziansyah (STIKES Suaka Insan, 2025)
Hypertension is one of the non-communicable diseases often referred to as a “silent killer”. In women of reproductive age, it is commonly caused by unhealthy lifestyle behaviors and hormonal imbalances. Hypertension can be managed through non-pharmacological therapies. One such therapy is consuming a decoction of soursop leaves. The intervention provided was an adjunct therapy to pharmacological treatment. This study aimed to investigate the effect of soursop leaf decoction on blood pressure among women of reproductive age with hypertension in the working area of Martapura 1 Health Center. A quantitative quasi-experimental method was used with a pre-test and post-test repeated measures design. The study involved 40 respondents selected through purposive sampling. Data were analyzed using the Wilcoxon test. The results showed a significant effect of soursop leaf decoction on both systolic and diastolic blood pressure, with a p-value of 0.000 (p < 0.005). These findings suggest that soursop leaf decoction effectively lowers blood pressure in hypertension women of reproductive age in the working area of Martapura 1 Health Center. This therapy is expected to serve as a potential alternative treatment for managing blood pressure in women of reproductive age with hypertension.